Globalisation - H.W. ARNDT (PSL Quarterly Review, 1998)
Globalisation, which was predicted by experts to do away with the nation state and create a single world market, has not turned out exactly as foretold. The most striking developments brought by the phenomenon have come in terms of faster transfer of goods and services across international borders, due in part to better communications and computer technology. Critics of globalisation still assert that it promotes inequality among classes, unfair competition, and undermines democracy. However, these criticisms can be seen as an aversion to foreign competition brought about by protectionist views. An attempt is made to develop a pragmatic interpretation of the globalisation phenomenon.